Getting ahead of the ageing curve: learning from EU experiences for a healthier demographic transition - Freitas, Hércules Rezende; Malva, João Oliveira (Frontiers in Public Health, 2025)
Population ageing is accelerating worldwide, with one in six people projected to be over 60 by 2030. This demographic shift is already evident in Europe, with slower life-expectancy gains, widening healthspan–lifespan gaps, and growing labour shortages. In this paper, we examine global projections, country-level disparities, evidence from economics, geroscience and public health to assess the conditions under which longevity can generate a net social dividend. Our analysis highlights recent advances in ageing research, including stem-cell, epigenetic and anti-inflammatory interventions, as well as meta-research efforts to promote community-driven consensus on strategic geroscience problems. Translating these insights into societal benefits require regulatory recognition of ageing as a treatable condition, equitable access to innovation, and living-lab ecosystems that connect bench discoveries to health and social care. Using fiscal modelling, we show that disability-driven expenditure could rise by as much as 2.7% of EU GDP annually by 2070, unless offset by slower biological ageing or managed migration. Finally, we suggest that European experiences, particularly from the Iberian Peninsula, can inform South American countries now entering rapid demographic transition.